Alleviating Worker Shortages Through Targeted Subsidies: Evidence from Incentive Payments in Healthcare - Gandhi, Ashvin D.; Olenski, Andrew; Ruffini, Krista; Shen, Karen (The Review of Economics and Statistics, 2024)
Abstract Worker shortages are common in many industries. This paper examines the effect of government subsidies to address these shortages in the context of a reform that tied Medicaid payments to nursing home staffing levels. We find that the reform substantially increased staffing, especially for facilities serving many Medicaid patients. Facilities responded primarily by hiring workers in lower-wage roles rather than increasing hours of incumbent or high-wage staff. This contrasts with null effects we estimate for a non-incentivized rate increase, suggesting that the incentive structure of government payments—rather than just the level—is key to boosting employment in sectors facing worker shortages.